Sistema de información web y la mejora en la gestión de comercialización de productos agrícolas en la empresa Negocios Corporativos IGUAZÚ S.A.C. de San José - Pacasmayo - Izquierdo Quispe, Daniel (2019)
The development of this thesis work called "Web Information System and the Improvement in the Management of Marketing of Agricultural Products in the company Empresas Corporativos Iguazú S.A.C. de San José - Pacasmayo”. It has been established as the main objective to improve the processes of purchase and sale of products produced by Negocios Corporativos Iguazú S.A.C., through the development and implementation of this web computer system. Currently, Iguazú Corporate Business does not have a Commercial Management Web System, so the processes are not well defined and are developed manually; this produces that there are great losses of time in registration and control in the processes of purchase, sale and warehouse in the company. That is why a solution is presented in the present investigation, where a study based on the RUP Methodology (Rational Unified Process) has been carried out, a methodology that has allowed us to generate an orderly and quality project; In the implementation of the system, Free Software, database (MySQL), PHP and JavaScript have been used as programming language, libraries and a cross-platform library (Bootstrap). In this study, a general design of the Quasi experimental research (Pre Test and Post Test) was carried out; where there is a manipulation of variables, all this is done following some established parameters, in which the independent variable is manipulated to perceive the effect on the dependent variable. The population of our research is focused on the users of the company; clients and administrative staff. The sample is taken according to the indicators, there are 06 administrative responsible for the main processes of the company (purchase, sale and warehouse). The instruments used in the present investigation are mainly: direct observations and surveys. With the development of the web computer system, the attention of a sale was reduced by 68.47%, in addition the time in the consultation of product stocks was reduced by 99.22%, and in the same way a reduction of 99.17% was achieved. Generation of management reports and finally the level of user satisfaction was increased by 42.96%.